Different phenotypes of the NAT2 gene influences hydralazine antihypertensive response in patients with resistant hypertension. (February 2014) - Spinasse, Lizania Borges; Santos, Adalberto Rezende; Suffys, Philip Noel; Muxfeldt, Elizabeth Silaid; Salles, Gil Fernando
Aim: Hydralazine, a vasodilator used in resistant hypertension (RH) treatment is metabolized by an acetylation reaction mediated by N -acetyltransferase 2, the activity of which depends on NAT2 polymorphisms. Our aim was to evaluate whether different acetylation phenotypes influenced the antihypertensive effect of hydralazine in patients with RH.Patients & methods: DNA samples from 169 RH patients using hydralazine were genotyped by sequencing the NAT2 coding region, and acetylation phenotypes were defined.Results: Sixty-five patients (38.5%) were intermediate, 60 (35.5%) slow and 21 (12.4%) fast acetylators. Twenty-three (13.6%) patients were indeterminate. Upon association analysis, only slow acetylators had significant blood pressure reductions after hydralazine use, with mean 24-h systolic and diastolic blood pressure reductions of 9.2 and 5.5 mmHg. Four patients presented hydralazine adverse effects resulting in drug withdrawal, three of them were slow acetylators.Conclusion: The slow acetylation phenotype, determined by polymorphisms within NAT2, influenced both the antihypertensive and adverse effects of hydralazine in RH. Original submitted 31 May 2013; Revision submitted 7 October 2013